The effect of external compression on the mechanics of muscle contraction - Wakeling, J. M.; Jackman, M.; Namburete, A. I. (Journal of Applied Biomechanics, 2013)
The velocity at which a muscle fascicle will shorten, and hence the force that it can develop, depends on its gearing within the muscle belly. Muscle fascicle length depends on both its pennation and the thickness of the muscle. It was expected that external compression would reduce the muscle thickness and pennation and thus cause a reduction to the gearing of the fascicles relative to the muscle belly. Structural properties of the medial gastrocnemius muscle were visualized using B-mode ultrasound in six subjects. Measurements were taken during cyclical isotonic contractions at three different ankle torques and with the application of no, one, or two elastic compression bandages to the lower leg. Ankle torques and angular velocities were unaffected by the external compression. External compression did, however, reduce the muscle thickness and the fascicle pennation and resulted in a decrease in the gearing within the muscle belly. Reductions in gearing would result in an increase in the muscle fascicle shortening velocity that would reduce the force-generating potential of the fascicles. It is suggested that externally applied compression should not be considered a way to enhance muscle performance when based on the structural mechanics.